2020
DOI: 10.21203/rs.3.rs-108681/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptability of Patient-centered Hypertension Education Delivered by Community Health Workers among People Living with HIV/AIDS in Rural Uganda

Abstract: Background The prevalence of hypertension is increasing among people living with HIV/AIDS (PLWHA) in low- and middle-income countries (LMICs). However, knowledge of the complications and management of hypertension among PLWHA in Uganda remains low. We explored the acceptability of implementing hypertension (HTN) specific health education by community health workers (CHWs) among PLWHA in rural Uganda. Methods We conducted a qualitative study consisting of 22 in-depth interviews (14 PLWHA/HTN and 8 CHWs), 3 focu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Patient education is more effective when tailored to a patient's individual needs, including two-way feedback between patient and care provider and using a variety of delivery approaches including printed materials [57], telephone based brief interactive sessions, group online education sessions, interactive digital tools and creating opportunities for peer-support [58][59][60][61]. These interventions can be effectively delivered by physicians, nurses, pharmacists or community health workers and in multidisciplinary teams [62,63]. For patients with low health literacy levels, strategies that use visual aids such as video or infographics; deliver self-management curriculum in small, more achievable instructional units; repeat intervention training; confirm learning or mastery; and provide corrective or tailored instruction until mastery is attained, improve achievement of CVD self-management behaviors [64].…”
Section: Patient Educationmentioning
confidence: 99%
“…Patient education is more effective when tailored to a patient's individual needs, including two-way feedback between patient and care provider and using a variety of delivery approaches including printed materials [57], telephone based brief interactive sessions, group online education sessions, interactive digital tools and creating opportunities for peer-support [58][59][60][61]. These interventions can be effectively delivered by physicians, nurses, pharmacists or community health workers and in multidisciplinary teams [62,63]. For patients with low health literacy levels, strategies that use visual aids such as video or infographics; deliver self-management curriculum in small, more achievable instructional units; repeat intervention training; confirm learning or mastery; and provide corrective or tailored instruction until mastery is attained, improve achievement of CVD self-management behaviors [64].…”
Section: Patient Educationmentioning
confidence: 99%
“…Prior studies in Tanzania have shown that HIV care delivery by CHWs is favorably received 34,35 . Furthermore, a few studies have also revealed that interventions offering NCD care delivered by CHWs are feasible, highly acceptable, and effective 36,37 . The utilization of CHWs to provide care may be an attractive strategy in a health care system that is overtaxed by high patient volumes and few prescribing providers 38,39 …”
Section: Discussionmentioning
confidence: 99%